PENGARUH BENTUK ROUTING PERPIPAAN SISTEM PENDINGIN PRIMER REAKTOR TRIGA KONVERSI TERHADAP PENURUNAN AKTIVITAS N-16 DI PERMUKAAN TANGKI REAKTOR - Wardhani, Veronica Indriati Sri; Rahardjo, Henky P. (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2016)
The conversion program in 2000 Bandung TRIGA reactor fuel from the cylinder into fuel plates needs a new reactor cooling system design. The design of the new reactor cooling system are devised in such away to not much changed from the existing reactor cooling system, regarding its space and location have no possibility to change. Therefore, pipe routing analysis is required to select the plate type TRIGA reactor cooling system, to meet the cooling requirements of the system, attempted to match with the existing space and location. According to the availability of the existing space, four (4) possibilities of pipe routing can be designed. From the four possibilities of pipe routing, then analyze the travel time of particles N-16, which emits gamma radiation from the core to the surface of the reactor tank. Analysis was performed by assuming a constant cooling fluid density (ρ) (incompressible fluid), the entire N-16 generated in the reactor core is transported to the surface of the reactor tank. The results show that the third alternative pipe routing is the most optimum, due to its approaching transport time is five (5) times the half-life of N-16 (36.7047 sec), so that its activities decreases from 100% to 3% (A/A0 = 0.0317) and the pipe length is still enough to put in the available space reactor cooling system.